Simple Fabrication of Anatase-Brookite Mixed-Phase TiO2 Nanoparticles with Visible-Light Responsive Photocatalytic Activity - Xue, Bin; Sun, Tao; Wu, Ji-Kui (Asian Journal of Chemistry, 2012)
Titanium dioxide (TiO2) nanoparticles with binary mixed-phase were fabricated by a hydrothermal process under broad temperature range (100-180 ºC). The as-fabricated TiO2 nanoparticles consist of rice-like nanocrystals with anatase-brookite mixed-phase. The ratios of anatase and brookite in the as-fabricated TiO2 nanoparticles are affected by hydrothermal temperature. The absorption bands of the as-fabricated TiO2 nanoparticles are distinctly red-shifted to visible light region. The as-fabricated TiO2 nanoparticles exhibited the superior photocatalytic activity under visible light irradiation. Due to adoption of stable TiCl3 as Ti sources, the fabrication route is simple and thus promotes large-scale production and application of mixed-phase TiO2 nanoparticles for visible light driven photocatalytic process.